Creep Properties of Walikukun (Schouthenia ovata) Timber Beams - Ali Awaludin; Ngudiyono Ngudiyono; Achmad Basuki (Civil Engineering Dimension, 2016)
This study presents an evaluation of creep constants of Walikukun (Schoutheniaovata) timber beams when rheological model of four solid elements, which is obtained byassembling Kelvin and Maxwell bodies in parallel configuration, was adopted. Creep behaviorobtained by this method was further discussed and compared with creep behavior developedusing phenomenological model of the previous study. Creep data of previous study was deformationmeasurement of Walikukun beams having cross-section of 15 mm by 20 mm with a clearspan of 550 mm loaded for three weeks period under two different room conditions: with andwithout Air Conditioner. Creep behavior given by both four solid elements model and phenomenological(in this case are power functions) had good agreement during the period of creepmeasurement, but they give different prediction of creep factor beyond this period. The powerfunction of phenomenological model could give a reasonable creep prediction, while for the foursolid elements model a necessary modification is required to adjust its long-term creep behavior.